1984
DOI: 10.1104/pp.76.3.638
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Effect of Cytokinin on Secondary Xylem Fiber Formation in an In Vivo System

Abstract: The regulatory effect of cytokinin on the formation of secondary xylem fibers was studied in the hypocotyl of young Helianthus annuus L. plants. Positive correlation was found between the kinetin supplied (0.25-0.5 micrograms/gram) to the growth medium and the rate of fiber formation within and between the vascular bundles. Reducing the root originated cytokinin supply, either by root removal or by lowering the transpiration rate, diminished the number of newly formed secondary xylem fibers. This decrease was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
1

Year Published

1989
1989
2023
2023

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 14 publications
0
19
0
1
Order By: Relevance
“…A potential mode for this enhanced translocation is the effect of cytokinin on xylem formation in soybean (Fosket and Torrey, 1969). Saks et al (1984) observed that partial removal of side roots and root apices inhibited the rate of secondary xylem formation in the hypocotyl of Helianthus. In addition, the exogenous addition of kinetin to the growth medium stimulated the rate of formation of secondary xylem fibers and vascular bundles.…”
Section: Discussionmentioning
confidence: 97%
“…A potential mode for this enhanced translocation is the effect of cytokinin on xylem formation in soybean (Fosket and Torrey, 1969). Saks et al (1984) observed that partial removal of side roots and root apices inhibited the rate of secondary xylem formation in the hypocotyl of Helianthus. In addition, the exogenous addition of kinetin to the growth medium stimulated the rate of formation of secondary xylem fibers and vascular bundles.…”
Section: Discussionmentioning
confidence: 97%
“…We show that both auxin and GA are required for cambium proliferation, but each induces different derivatives: Auxin promotes the development of vessel elements only below the site of application, while GA induces xylem fiber formation both above and below the source. Since it is known that cytokinin-regulated xylogenesis is necessary for fiber development (Aloni, 1982;Saks et al, 1984;Matsumoto-Kitano et al, 2008), we assume that both GA and cytokinin signaling are required for the initiation and maturation of fiber cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although high concentrations of auxin stimulated rapid differentiation of short fibers with thick secondary walls, high levels of GA resulted in long fibers with thin walls. In addition, both in vivo and in vitro experiments have demonstrated that cytokinin transported from root apices is also required for fiber differentiation in stems (Saks et al, 1984). For example, the number of newly differentiated fibers decreased significantly by removal of root apices or by lowering the transpiration rate, and this decrease could be reversed by the application of cytokinin.…”
Section: )mentioning
confidence: 99%